تَنویرُ الذَّاتِ بالمنتَخبَاتِ من مَسائِل النحوِ في سُورةِ المرسَلاتِ (Journal of the College of Education for Women, 2019)
That grammatical studies, a phenomenon of the Arabic language,enabling the researcher during his research of the development of sentences,textual analysis, to be the result of that meaning semantic of a sentence, andthe statement of the function the individual, in terms of its meaning incontext, and a link to the meaning lexical give indications of the currentsingle, and correlation analysis II , in terms of significance with the currentstatus syntactic to that individual, and these of the most important features ofgrammatical studies of modern, based on the relationship structure sense, andthe relationship of the meaning of the structure, we looked for Aiklo for sucha study, Koran, all meanings and connotations, the incapability of theresearchers on the analysis of texts, as Menhala thirst tortured him andAlbulagjun GrammariansThe Sura transmitters goal of our research, and our desire to maintaina curriculum balanced in guiding the significance of the moral of the statesprecious in the sura of findings, analysis, and direct the individual to thepoint of syntactic good, commensurate with the meaning of the verse, and theresearch has examined some of the grammatical issues, and directing some ofthe readings, and a statement approval of the meaning, and properinstallation, and research has included the introduction, we have spokenabout the importance of study grammar, and language of the Koran holybook miraculous immortal, and then mentioned the importance of choosingthe researcher to the subject matter, and having completed the front so weopened the Find prologue, we pointed out where the reason for naming Sura ,arranged between the fence, and the virtues of dignity for Al through theconversations in this regard, after this preface the brief, was our approach toissues of grammar contained in the sura, and display the differences, and theevidence of grammatical and directed to the appropriate destination for theappropriate Holy verses in the sura, according to scientific analysis issupported with evidence and proofs , The researcher concludes with aconsideration of the results through the supply and extraction, one of thethings, scientific research, in order to put the researcher a starting point forresearch may be more comprehensive than our present.